Migration and health: Examining the linkages through a gender lens - Jasmine Gideon (United Nations Research Institute for Social Development (UNRISD), 2015)
Analysing migration through a gender lens involves understanding the social relations and norms that influence womens and mens roles and responsibilities, and their differential access to resources and services. Gendered norms around men and womens roles and responsibilities have also shaped migration processes and debates. Migration has often been regarded as a predominantly male phenomenon, with men migrating for work, while women - when they migrate - are often viewed as dependent family members. Yet the evidence points to large flows of independent female migrants globally. These global trends are reflected in the Chinese context where migration research has pointed to processes of feminization and found that many women do in fact migrate independently and as primary breadwinners. Given womens gendered responsibilities of caring for other family members - including children, the sick and elderly - migration can potentially affect not only the health and well-being of the female migrants themselves, but also other family members (whether migrants or those left behind). The paper discusses the tensions between the feminization of migration and the domestic roles women typically assume, including unpaid care work. It then examines issues related to health of migrants, through a gender lens. Discussion primarily focuses on some key areas that have particular resonance in debates around the health and well-being of migrants - occupational health and work, sexual and reproductive health, and mental health. The paper then moves on to a more detailed analysis of the impact of womens domestic roles - particularly unpaid care work - in the context of migration and consider the implications of this for health and health care. It concludes by considering what potential migration offers for changing gender norms and reflects on the implications of the global debates raised in this paper for the Chinese context.
Keywords: 330